Seorang Wanita dengan Pneumokoniosis yang Mengalami Komplikasi Trapped Lung dan Dilakukan Dekortikasi: [Decortication of Trapped Lung in Pneumoconiosis Patient: A Case Report] - Tutik Kusmiati; Winariani Koesoemoprodjo; Novita Maulidiyah (Faculty of Medicine Universitas Airlangga, 2017)
Background: Pneumoconiosis is an occupational lung disease caused by dust inhalation which deposit in lung parenchym and cause lung fibrosis. Trapped lung is impairment of compliance because of pleural inflammation. Case: We presented a diagnostic problem case of a woman, 37 years old who worked at coffee factory for 20 years as a coffee powder packer. Patient came in previous hospital with continous dispnea not relieved by rest or medication. She had been diagnosed with pneumothorax and already treated with chest tube for 2 weeks but there was no improvement. Patient was reffered to Dr. Soetomo hospital and treated with continous suction and chest physiotherapy for 2 months but there was no improvement. Patient then underwent thoracoscopy to find the cause of persistent collapsed lung. Thoracoscopy showed blackish leucoplaque pleural biopsy was done histopathological result showed pneumoconiosis. CT Scan showed fluidopneumothorax and severe lung restriction. The patient then underwent torachotomy and decortication which showed attachment of medial, inferior, and posterior lobe of left lung and organized pleural effusion. Post operation, the lung expanded completely and patient condition improved. Conclusion: Lung entrampment rarely become the complication of pneumoconiosis. Early diagnosis and appropriate treatment will avoid further complication.